Peran Yayasan Al-Amanah Indonesia Kota Bekasi Dalam Memberdayakan Penyandang Tuna Netra Buta Huruf Al-Quran Melalui Pembinaan Baca dan Hafalan Al-Qur’an - Ahmad Maulana; Abdiyansyah (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2025)
Research Objective: This study aims to explain the role of Al-Amanah Indonesia Foundation Jatiasih, Bekasi City in empowering the visually impaired through Qur’an reading and memorization programs. Research Method: Qualitative. Research Summary: The Al-Amanah Indonesia Foundation Jatiasih conducts structured and ongoing Qur’an education programs for the visually impaired, focusing on reading and memorization. These initiatives include Braille Qur’ans, inclusive learning spaces, professional instructors, daily meals, and transportation aid. In memorization, the foundation also provides trained mentors, learning materials, uniforms, and meals. The program seeks to enhance spiritual and social capacity, promote equal religious access, and encourage independence rooted in Islamic values and community empowerment. Conclusion: The Al-Amanah Indonesia Foundation plays an active and comprehensive role in addressing the spiritual, social, and practical needs of the visually impaired. Field findings indicate that this role aligns with role theory, the foundation’s mission, and the principles of disability empowerment in both Islamic and societal contexts. Keywords: Al-Amanah Indonesia Foundation, Visually Impaired, Qur’an Education, Empowerment